Peering through the haze: - Rosangela Aparecida Soares Fernandes; Leonardo Bispo de Jesus Júnior; Victor Henrique Lana Pinto (Revista de Defesa da Concorrência)
Objective: the aim of this article was to detect economic signs of cartel in the resale of LPG in the Brazilian cities of Campina Grande-PB, Caruaru-PE, Jaboatão dos Guararapes-PE, and Recife-PE; the first market condemned by the Administrative Council for Economic Defense (Cade).